CARCASS CHARACTERISTICS OF BROILER CHICKENS FED ACHA HUSK AS REPLACEMENT FOR WHEAT OFFAL - Chomo , F. K.; Kalla, D. J. U.; Igila, T. T.; Jatutu, S. S. (Nigerian Journal of Animal Production, 2024)
The study was conducted to evaluate the carcass traits of broiler chickens fed acha husk in place of wheat offal. Five different varying levels of acha husk were used in formulating the diets. The design used for the experiment was a completely randomized design. Birds were managed under the deep litter system for a period of 6 weeks. At the end of the experiment, four birds were randomly selected from each treatment for carcass evaluation. The values obtained were subjected to statistical analysis and the results showed that there were significant differences (p>0.05) in some of the parameters such as eviscerated weight, gizzard, liver, heart and spleen where birds on the acha husk base diets did better than the control diet. However, no significant differences were noted in the lungs, small intestine and large intestine of broiler birds under different treatments of acha husk. It was therefore concluded that using acha husk in place of wheat offal in broiler chickens’ diets at 24.20% level produced broilers of better carcass traits compared to that fed wheat offal under conventional commercial feeds (p>0.05)